(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study investigates the perceptions and socio-political support of external stakeholders toward Initao College, a locally funded college in Misamis Oriental, Philippines. Utilizing purposive sampling, 80 respondents from four stakeholder groups—students, alumni, parents, and residents—were selected to participate in the research. The data was collected using the Institutional Sustainability Survey, which assesses the effectiveness of the institution’s programs and services across five key result areas outlined by the Commission on Higher Education (CHED). These areas include Governance and Management, Quality of Teaching and Learning, Professional Exposure and Research, Support for Students, and Community Relations. The results highlight the need for improvements in stakeholder awareness of the college’s Vision, Mission, Goals, and Objectives (VMGO). Recommendations include enhancing communication strategies, aligning perceptions through workshops, increasing the visibility of VMGO, fostering greater stakeholder involvement, and strengthening community engagement. Additionally, the study recommends establishing a system for regular feedback to guide the institution’s continuous improvement efforts. The findings suggest that more comprehensive strategies for engagement and communication are essential for Initao College’s institutional sustainability and stakeholder alignment.